Effectiveness and Tolerability of a Patch Containing Onion Extract and Allantoin for Cesarean Section Scars - Conti, Valeria; Corbi, Graziamaria; Iannaccone, Teresa; Corrado, Bianca; Giugliano, Luigi; Lembo, Serena; Filippelli, Amelia; Guida, Maurizio (Frontiers in Pharmacology, 2020)
The prevention or early treatment of pathological scars is the most appropriate therapeutic approach. Gels and patches containing onion extract and allantoin are safe and effective in patients with scars of various origins and severity. However, no controlled studies have evaluated the effects of the patch formulation in women after Cesarean delivery. This study aimed to investigate the effects of a patch containing Allium cepa and allantoin on Cesarean section (C-section) scars This is an observational study. Women were consecutively recruited at the University Hospital of Salerno and subdivided into two groups considering the number of C-section. Group A included subjects without and group B with a history of C-section. Scars assessment was made using digital photographs and the Patient and Observer Scar Assessment Scale (POSAS). After 4 weeks, the C-section of the women who had applied a patch containing Allium cepa and allantoin and those of women who had not used any products (controls) were re-evaluated as at baseline. The Observers independently performed the scars assessment at baseline and after 4 weeks. Data are expressed as the difference of the POSAS scores after 4 weeks minus the POSAS scores at baseline. The statistical significance was established at a p-value <0.05. Ninety-three subjects completed the study (47 in group A and 46 in group B). Women who had used a patch showed an improvement in total score by observer scale when compared with controls (p=0.013). By the patient scale, no significant changes from baseline were found in group A and group B. Group B with patch showed changes in scars’ pigmentation (p=0.015), relief (p=0.039) and pliability (p=0.046) in comparison of controls. Digital photographs confirmed such improvements in women who had already undergone previous C-section, while no significant changes from baseline were found in women without a history of C-section. Intense treatment of just 4 weeks with a patch containing Alium Cepa extract and allantoin was able to improve pigmentation, relief, and pliability of C-section scars in women with a history of C-section.